Relatives marriage and its genetic effect on children (Journal of the College of Education for Women, 2019)
Marriage is a characteristic of the human race, as it is one of the oldest organization, asoldas human beign marrige is a legitimale relationsbip between male and female in the name of Allah "o mankind !Be dutiful to your lord, Who created you from a single person (Adam), and from him (Adam) He created his Wife (Eve), and from them both He created mang men and womenMarriage is a requirement of human life to ensure tle continuity and survival of the human species and established it in a legal, social and legitimate frame,according to certain criteria and conditions so that the individual earns psychological and social comfort in the name of Allah and Allah has made for you Azwaj ( mates or wives), sons and grand sons, and has bestowed on you good provision"Marriage in Irag has been no longer reachable to every young people because marrige is a phenomenon affected by series of changes that have taken place in hraqi society which is summedup in different economic and social crises. These circumstances, developments and changes that experienced by Iraqi society leads to a relatives marriage sample appearanceFrom thist the researcher tried to see the effect of relative marriage effectness on the health of the newborn from diseases.